2013
DOI: 10.1371/journal.pone.0075231
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Visual N1 Latencies in Expert Video-Game Players: A Temporal Basis of Enhanced Visuospatial Performance?

Abstract: Increasing behavioural evidence suggests that expert video game players (VGPs) show enhanced visual attention and visuospatial abilities, but what underlies these enhancements remains unclear. We administered the Poffenberger paradigm with concurrent electroencephalogram (EEG) recording to assess occipital N1 latencies and interhemispheric transfer time (IHTT) in expert VGPs. Participants comprised 15 right-handed male expert VGPs and 16 non-VGP controls matched for age, handedness, IQ and years of education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(65 reference statements)
2
15
0
1
Order By: Relevance
“…This is consistent with electroencephalogram evidence, which has established that, compared to nVGPs, individuals who played video games before the age of 10 showed earlier N1 latencies (an event-related potential reflecting faster discrimination of visual stimuli), suggesting a more efficient operation of visual attentional resources (Latham, Patston, Westermann, Kirk, & Tippett, 2013). Similarly, developmental studies have demonstrated that cognitive plasticity and traininginduced cognitive improvements generally decline with age (e.g., Baltes & Kliegl, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with electroencephalogram evidence, which has established that, compared to nVGPs, individuals who played video games before the age of 10 showed earlier N1 latencies (an event-related potential reflecting faster discrimination of visual stimuli), suggesting a more efficient operation of visual attentional resources (Latham, Patston, Westermann, Kirk, & Tippett, 2013). Similarly, developmental studies have demonstrated that cognitive plasticity and traininginduced cognitive improvements generally decline with age (e.g., Baltes & Kliegl, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…While the performance of experienced-VGPs was consistent with previous research (e.g. Latham et al 2013cLatham et al , 2014, the performance of non-VGPs performance was not. This might indicate the leftvisual-field performance bias is not entirely typical of the general population.…”
Section: Discussionsupporting
confidence: 86%
“…Earlier N100 latencies in the visual pathways are another feature found in long-term VGPs, which may contribute to faster response times in visual tasks after years of practice (Latham et al, 2013). …”
Section: Discussionmentioning
confidence: 99%